2020
DOI: 10.1111/ejn.14836
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Stress‐induced Hyperthermia in SNAP25Δ3 mice, a mouse model with disabled Gβγ regulation of the exocytotic fusion apparatus

Abstract: Behavioral assays in the mouse can show marked differences between male and female animals of a given genotype. These differences identified in such preclinical studies may have important clinical implications. We recently made a mouse model with impaired presynaptic inhibition through Gβγ‐SNARE signaling. Here, we examine the role of sexual dimorphism in the severity of the phenotypes of this model, the SNAP25Δ3 mouse. In males, we already reported that SNAP25Δ3 homozygotes demonstrated phenotypes in motor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…We assessed whether disabling the Gβγ-SNARE interaction alters the response to physiologic stressors, since we had previously reported that Snap25 Δ3/Δ3 mice had an altered behavioral response to acute physiological stressors, specifically elevated stress-induced hyperthermia ( 16 , 25 ). We performed calorimetric studies in which energy expenditure and feeding behavior in chow-fed Snap25 +/+ and Snap25 Δ3/Δ3 mice were measured at a standard housing temperature (22°C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed whether disabling the Gβγ-SNARE interaction alters the response to physiologic stressors, since we had previously reported that Snap25 Δ3/Δ3 mice had an altered behavioral response to acute physiological stressors, specifically elevated stress-induced hyperthermia ( 16 , 25 ). We performed calorimetric studies in which energy expenditure and feeding behavior in chow-fed Snap25 +/+ and Snap25 Δ3/Δ3 mice were measured at a standard housing temperature (22°C).…”
Section: Resultsmentioning
confidence: 99%
“…The mice were then exposed to an acute cold challenge (6°C) to assess whether they could mount a physiologic response by increasing energy expenditure and food intake. assessed whether disabling the Gβγ-SNARE interaction alters the response to physiologic stressors, since we had previously reported that Snap25 Δ3/Δ3 mice had an altered behavioral response to acute physiological stressors, specifically elevated stressinduced hyperthermia (16,25). We performed calorimetric stud- Protection from HFD-induced obesity and adiposity in Snap25 Δ3/Δ3 mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al [ 26 ] reported that SNAP25 rs362987 polymorphisms significantly increase ADHD risk. Sex differences in altered stress responses were reported in SNAP25 mutant mice [ 27 ]. Similarly, some CDH13 SNPs, which negative regulator of axon growth during neural differentiation, were revealed to contribute ADHD pathophysiology, particularly rs6565113 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of chronic, global disruption of the Gβγ-SNARE interaction have been studied in the mouse as a model system. Mutagenesis of SNAP25 to a mutant SNAP25Δ3 that interacts less well with Gβγ leads to physiological consequences, including deficits in stress processing and depressive phenotypes 16,22 .…”
Section: Introductionmentioning
confidence: 99%